2021
DOI: 10.21203/rs.3.rs-664932/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Flexible Microstrip Patch Antenna with Different Conductive Materials For Telemedicine and Mobile Biomedical Imaging Systems

Abstract: Telemedicine and mobile healthcare communication devices require compact antennas with superior performance and reduced size and weight. The design and development of such antennas for broadband applications are challenging for many researchers. In this study, a wearable rectangular microstrip antenna was designed and implemented to detect many tumors. The patch and ground part of the antenna, which can be used as both a transmitter and a receiver in microwave imaging systems, are made of copper tape, graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Metode slot pada antena berhasil membentuk dan menghasilkan respon dual band yang diinginkan. E. A. Aydın dan E. A. Aydin, [4] dalam jurnal "A Novel Flexible Microstrip Patch Antenna with Different Conductive Materials For Telemedicine and Mobile Biomedical Imaging Systems," penerapan program CST Studio dilakukan untuk mengoptimalkan parameter antena. Antena microstrip konvensional memiliki pita sempit dan penguatan rendah.…”
Section: Pendahuluanunclassified
“…Metode slot pada antena berhasil membentuk dan menghasilkan respon dual band yang diinginkan. E. A. Aydın dan E. A. Aydin, [4] dalam jurnal "A Novel Flexible Microstrip Patch Antenna with Different Conductive Materials For Telemedicine and Mobile Biomedical Imaging Systems," penerapan program CST Studio dilakukan untuk mengoptimalkan parameter antena. Antena microstrip konvensional memiliki pita sempit dan penguatan rendah.…”
Section: Pendahuluanunclassified
“…Antenna parameters Antenna-1 (Circular microstrip patch antenna) [21] Antenna-2 (Microstrip patch antenna) [22] Antenna-3 (Hexagonal Microstrip antenna) [ The comparison Table 3 shows the comparison of fabricated PVC-based substrate antenna with existing flexible antennas in literature, it has been observed that the gain of PVC substrate antenna is comparatively more than PDMS, felt, and foam-based substrate antennas. Even the return loss obtained is better than existing antennas.…”
Section: Table 3 Comparison With Existing Flexible Antennasmentioning
confidence: 99%
“…As an alternative, textile antennas made of felt material can be used as a non-invasive and nonradiation solution for detecting the depth of breast tumours. Textile antennas are flexible antennas made of textile material and can be configured in various shapes and sizes [9][10][11]. This study chose a textile antenna made of felt material because it has several advantages, such as good mechanical strength and the ability to capture microwaves effectively.…”
Section: Introductionmentioning
confidence: 99%